Distribution of postganglionic neurons which contain dopamine β-hydroxylase, tyrosine hydroxylase, neuropeptide Y and vasoactive intestinal polypeptide in the human middle cervical ganglion. (June 2019) - Kokubun, Souichi; Sato, Tadasu; Yajima, Takehiro; Ichikawa, Hiroyuki
Highlights: Human middle cervical ganglion had neuronal cells in sympathetic trunk. These neurons contained catecholamine-synthesizing enzymes and neuropeptides. They were abundantly immunoreactive for DBH, TH and NPY. However, VIP-containing neurons were relatively rare. Some neurons are probably non-catecholaminergic in human middle cervical ganglion. Abstract: The middle cervical ganglion (MCG) has been shown to contain neurotransmitters and related substances in the cat, dog and sheep. However, little is known about their presence or distribution in the human MCG. In this study, immunohistochemistry for catecholamine-synthesizing enzymes and neuropeptides was performed on the MCG in human cadavers. In 4 samples of human cadavers, MCG swellings contained numerous postganglionic neurons. In another sample, a distinct swelling of the MCG could not be detected. However, neuronal cell bodies were present within the sympathetic nerve trunk between the superior cervical and stellate ganglia. The cell size analysis demonstrated that cell bodies of postganglionic neurons measured 94.1–1774.1 μm 2 (mean ± S.D. = 578.1 ± 127.7 μm 2 ) in the MCG. Postganglionic neurons in the MCG were immunoreactive for dopamine β-hydroxylase (DBH, 92.1%), tyrosine hydroxylase (TH, 59.3%), neuropeptide Y (NPY, 71.9%) and vasoactive intestinal polypeptide (VIP, 19.3%). TH-positive neurons in the human MCG appear to be infrequent compared to the sheep MCG in a previous study. In the superior cervical (SCG) and stellate ganglia (SG), 91.0% and 94.2%, respectively, of postganglionic neurons showed DBH-immunoreactivity. A total of 83.8% and 70.4%of them contained TH-immunoreactivity in the SCG and SG. However, expression of NPY in the SG (78.2%) was more abundant than in the SCG (59.1%). Only 16.4% and 13.8% of postganglionic neurons were immunoreactive for VIP in the SCG and SG, respectively. VIP-immunoreactivity was also expressed by nerve fibers surrounding some postganglionic neurons in the MCG (8.7%), SCG (11.5%) and SG (5.9%). The present study suggests that catecholamine, NPY and VIP are neurotransmitters in the MCG, SCG and SG of the human.